Safety and immunogenicity of a candidate Middle East respiratory syndrome coronavirus viral-vectored vaccine: a dose-escalation, open-label, non-randomised, uncontrolled, phase 1 trial - Folegatti, PM; Bittaye, M; Flaxman, A; Lopez, FR; Bellamy, D; Kupke, A; Mair, C; Makinson, R; Sheridan, J; Rohde, C; Halwe, S; Jeong, Y; et al. (Elsevier, 2020)
Background: Cases of Middle East respiratory syndrome coronavirus (MERS-CoV) infection continue to rise in the Arabian Peninsula 7 years after it was first described in Saudi Arabia. MERS-CoV poses a significant risk to public health security because of an absence of currently available effective countermeasures. We aimed to assess the safety and immunogenicity of the candidate simian adenovirus-vectored vaccine expressing the full-length spike surface glycoprotein, ChAdOx1 MERS, in humans.